Characterization and Development of Universal Ventricular Assist Device: Computational Fluid Dynamics Analysis of Advanced Design. Issue 8 (10th November 2021) - Goodin, Mark S.; Showalter, Michael S.; Horvath, David J.; Kuban, Barry D.; Flick, Christine R.; Polakowski, Anthony R.; Fukamachi, Kiyotaka; Karimov, Jamshid H.
Abstract : We are developing a universal, advanced ventricular assist device (AVAD) with automatic pressure regulation suitable for both left and right ventricular support. The primary goal of this computational fluid dynamics (CFD) study was to analyze the biventricular performance of the AVAD across its wide range of operating conditions. An AVAD CFD model was created and validated using in vitro hydraulic performance measurements taken over conditions spanning both left ventricular assist device (LVAD) and right ventricular assist device (RVAD) operation. Static pressure taps, placed throughout the pump, were used to validate the CFD results. The CFD model was then used to assess the change in hydraulic performance with varying rotor axial positions and identify potential design improvements. The hydraulic performance was simulated and measured at rotor speeds from 2, 300 to 3, 600 revolutions/min and flow rates from 2.0 to 8.0 L/min. The CFD-predicted hydraulic pressure rise agreed well with the in vitro measured data, within 6.5% at 2300 rpm and within 3.5% for the higher rotor speeds. The CFD successfully predicted wall static pressures, matching experimental values within 7%. High degree of similarity and circumferential uniformity in the pump's flow fields were observed over the pump operation as an LVAD and an RVAD. A secondary impeller axial clearance reduction resulted in a 10% decrease in peak flow residence time and lower static pressures on the secondary impeller. These lower static pressures suggest a reduction in the upwards rotor forces from the secondary impeller and a desired increase in the pressure sensitivity of the pump. The CFD analyses supported the feasibility of the proposed AVAD's use as an LVAD or an RVAD, over a wide range of operating conditions. The CFD results demonstrated the operability of the pump in providing the desired circumferential flow similarity over the intended range of flow/speed conditions and the intended functionality of the AVAD's automated pressure regulation.